From Export Promotion to Internationalization - International Trade Centre (United Nations, 2015)
Proceedings of 2014 Trade Promotion Organizations (TPO) Network World Conference and Awards held in Dubai, United Arab Emirates, on 3 - 5 November 2014, addressing the theme ‘From export promotion to internationalization’, reflects the debates, discussions and key messages of the conference and showcases the winners of the 2014 TPO Network Awards; reviews the recent trend in the business support environment to merge trade and investment activities; discusses the benefits and opportunities for TPOs and their beneficiaries such as trade facilitation, diversifying exports towards emerging markets and integrating SMEs into value chains.